POLITENESS STRATEGIES IN CELEBRITY TALK SHOW INTERACTION: A PRAGMATIC ANALYSIS OF JIMMY FALLON’S INTERVIEW WITH ROSÉ (BLACKPINK) - Fajriyah, Azkia Nurul; Amaliah, Fitri; Agus, Cecep (Universitas Muhammadiyah Lampung, 2026)
Despite the growing prevalence of cross-cultural celebrity interviews in globalized entertainment media, existing pragmatic research has predominantly examined either mono-cultural interactions or applied single theoretical frameworks, leaving the communicative complexity of hybrid cultural identities in Western talk show contexts insufficiently explored. The intersection of Korean hierarchical indirectness, Australian casualness, and American entertainment conventions within a single interaction represents a particularly under-examined configuration in politeness scholarship, creating a significant analytical gap that the present study seeks to address. This study examines politeness strategies employed in a celebrity talk show interaction between Jimmy Fallon and Rosé from BLACKPINK, applying both classical and contemporary politeness theories to analyze cross-cultural communication in media discourse. Adopting a qualitative descriptive design, the research draws on the complete transcript of the interview as its primary data source, comprising 42 coded utterances systematically analyzed through Brown and Levinson's politeness framework alongside contemporary extensions including rapport management theory and the concept of politic behavior. The findings reveal that positive politeness strategies dominate the interaction at 50%, reflecting the genre's emphasis on rapport-building and audience engagement, while negative politeness strategies constitute 33%, primarily through hedging and indirect questioning. Bald on record strategies appear in 12% of utterances during task-oriented segments, and off-record strategies comprise 5%, employed for humorous effects. The analysis demonstrates how Rosé's hybrid cultural identity Korean, Australian, and international manifests in sophisticated code-switching between different politeness norms, balancing Korean-influenced indirectness with Australian casualness. Jimmy Fallon adapts typical American talk show conventions to accommodate cross-cultural dynamics, demonstrating cultural sensitivity alongside enthusiastic entertainment. The study confirms that successful celebrity interviews require collaborative face-work and dynamic adjustment of linguistic strategies across changing interactional demands, contributing to pragmatic theory while offering practical implications for media professionals, intercultural communication practitioners, and scholars interested in K-pop's global media presence.